USO DE GEL HIDRORRETENTOR NO CULTIVO DO QUIABO (ABELMOSCHUS ESCULENTUS L.) EM SISTEMA DE SEMEADURA DIRETA - Henrique Dias Rodrigues , Pedro; Hayd Rego, Norton; Almeida dos Santos Espindola, Gabriella; Luiz Carpinedo Gomez, Aurelio; de Sá Strang, Rafael (ANAIS DO ENIC, 2026)
-